2016
DOI: 10.1093/aob/mcw201
|View full text |Cite
|
Sign up to set email alerts
|

Passive warming reduces stress and shifts reproductive effort in the Antarctic moss,Polytrichastrum alpinum

Abstract: Background and Aims The Western Antarctic Peninsula is one of the most rapidly warming regions on Earth, and many biotic communities inhabiting this dynamic region are responding to these well-documented climatic shifts. Yet some of the most prevalent organisms of terrestrial Antarctica, the mosses, and their responses to warming have been relatively overlooked and understudied. In this research, the impacts of 6 years of passive warming were investigated using open top chambers (OTCs), on moss communities of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
19
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 99 publications
(105 reference statements)
6
19
1
Order By: Relevance
“…Each panel has five holes of 1 cm in diameter to allow for improved airflow and avoid excessive warming. The OTCs were previously tested for 2 years for resistance to Antarctic climatic conditions and are similar in design to others used in Signy and Anchorage Islands, Antarctica . Each corresponding control was demarcated region of the same size and shape as the OTC footprint within ∼3.0 m of each OTC.…”
Section: Methodsmentioning
confidence: 99%
“…Each panel has five holes of 1 cm in diameter to allow for improved airflow and avoid excessive warming. The OTCs were previously tested for 2 years for resistance to Antarctic climatic conditions and are similar in design to others used in Signy and Anchorage Islands, Antarctica . Each corresponding control was demarcated region of the same size and shape as the OTC footprint within ∼3.0 m of each OTC.…”
Section: Methodsmentioning
confidence: 99%
“…Casanova-Katny et al (2016) found significant increases in sporophyte production in P. alpinum under passive warming OTC treatments after seven years of experimental warming, however we found no sporophytes in P. alpinum during our study. Our results are similar to those of Shortlidge et al (2016), who found increases in individual female and male gametangia production, but no increase in sporophyte production, in P. alpinum which suggests that warming may relieve environmental constraints on reproductive effort. Sexual reproduction in mosses may be limited by many factors such as spermlimitation (Rydgren et al 2006), resource limitation (Stark et al 2000(Stark et al , 2009 , and abiotic stress (Bowker et al 2000, Eppley et al 2011.…”
Section: Positive Effects Of Warming On P Alpinum Reproductive Biologysupporting
confidence: 89%
“…Our study is one of only two other studies to our knowledge that explores the effects of warming on moss reproductive output (Casanova-Katny et al 2016, Shortlidge et al 2016. We found that P. alpinum in warmed (OTC) plots exhibited significantly more female sex expression than control plots (Table 4.2 & Figure 4.8), similar to findings in two other Antarctic bryophyte studies (Casanova-Katny et al 2016, Shortlidge et al 2016). Casanova-Katny et al (2016) found significant increases in sporophyte production in P. alpinum under passive warming OTC treatments after seven years of experimental warming, however we found no sporophytes in P. alpinum during our study.…”
Section: Positive Effects Of Warming On P Alpinum Reproductive Biologysupporting
confidence: 83%
See 2 more Smart Citations